Student Perceptions in Using Sisfo E-Learning Applications at PGRI Palembang University - Diana Widhi Rachmawati; Erma Yuliani; Nuryanti Permata Sari; Mardiana Sari; Ida Suryani (STAI Hubbulwathan Duri, 2022)
Access to learning that is not limited by space and time must continue even though during the COVID-19 emergency, lecturers and students are required to prepare devices for learning from home and PGRI Palembang University has facilitated by using an application called E-Learning Sisfo. Although the use of e-learning as a learning medium in higher education is not yet optimal, it has become one of the interesting things to be researched so that a study was conducted to determine the perceptions of students of the Accounting Education Study Program in using SISFO. E-learning network application at FKIP PGRI Palembang University. The sample in this study is a student majoring in Accounting who uses e-learning in the lecture process where data is collected by means of a questionnaire or questionnaire and analyzed using the regression method. The results of the regression test show that the perception of students of the Accounting Education Study Program. Based on the results of the study, it can be concluded that the perception of students of the Accounting Education Study Program in using the e-learning application SISFO at PGRI Palembang University is an average of seventy three point fifty percent in the high category. and have good motivation in using e-learning as a learning medium.